Back Cover: Benzoxazepines Achieve Potent Suppression of IL‐17 Release in Human T‐Helper 17 (TH17) Cells through an Induced‐Fit Binding Mode to the Nuclear Receptor RORγ (ChemMedChem 2/2016). Issue 2 (19th January 2016) - Olsson, Roine I.; Xue, Yafeng; von Berg, Stefan; Aagaard, Anna; McPheat, Jane; Hansson, Eva L.; Bernström, Jenny; Hansson, Pia; Jirholt, Johan; Grindebacke, Hanna; Leffler, Agnes; Chen, Rongfeng; et al.
Abstract : The back cover picture shows structures of the retinoic acid‐related orphan receptor gamma (RORγ) with inverse agonist15 [left, red; 2‐chloro‐6‐fluoro‐ N ‐(4‐{[3‐(trifluoromethyl)phenyl]sulfonyl}‐2, 3, 4, 5‐tetrahydro‐1, 4‐benzoxazepin‐7‐yl)benzamide)], and with agonist25 [right, blue, ( N ‐(2‐fluorophenyl)‐4‐[(4‐fluorophenyl)sulfonyl]‐2, 3, 4, 5‐tetrahydro‐1, 4‐benzoxazepin‐6‐amine )]. Both an induced fit and an H‐bond to His 479 are necessary to disrupt the agonist conformation of the receptor, and it only takes minor structural changes to convert an inverse agonist into an agonist. These novel benzoxazepine‐based ligands for RORγ inhibit interleukin‐17 secretion with nanomolar potency. More information can be found in the Full Paper by Frank Narjes et al. onpage 207 in Issue 2, 2016 (DOI:10.1002/cmdc.201500432 ).